PROJECT METHOD IN THE PROCESS OF FORMING THE LEGAL COMPETENCE OF FUTURE TEACHERS OF ELEMENTARY SCHOOL - Vitіuk Valentyna (Mountain School of Ukrainian Carpaty, 2020)
In the context of relevant requirements for the training of future primary school teachers of the New Ukrainian School, the role of professional linguistic training of primary school teachers is increasing. The purpose of the article is to illuminate the essence of the method to the project, to describe the types of projects, the stages of work on the project and the possibilities of its application in the formation of the spelling of the competence of students of higher education institutions. To achieve the goal, the following research methods were used: theoretical: analysis and synthesis in the processing of linguistic, pedagogical and methodological literature on the problem under study; theoretical understanding and generalization of the experience of philologists and their own work experience to determine the state of work on the formation of the spelling of the competence of future primary school teachers; empirical: observation and analysis of classes in the discipline "Workshop on Ukrainian spelling" for students majoring in "Primary education". The article is revealed the different interpretations of the concept, is described the importance of design activity in the process of forming key and subject competencies of specialists. In scientific intelligence, the most common classifications of educational projects are analyzed, the structure of the method for the project in the writings of famous Ukrainian teachers and linguodidacts is described, attention is focused on assessing the level of students' project completion, an algorithm for working on a project for students is concluded, a sample project is proposed. As a result of the analysis of the problem, we came to the conclusion that in the conditions of modernization of education, updating its content and structure, new forms and teaching methods are particularly relevant, in particular, the project method, which helps students to develop skills to independently acquire knowledge and skills to apply the acquired spelling knowledge in specific communicative situations.